Identification of a fall armyworm (Spodoptera frugiperda)-specific gene and development of a rapid and sensitive loop-mediated isothermal amplification assay - Osabutey, A.F.; Seo, B.Y.; Kim, A.Y.; Ha, T.A.T.; Jung, J.; Goergen, Georg E.; Owusu, E.O.; Lee, G.S.; Koh, Y.H. (Springer, 2022)
The fall armyworm [FAW, Spodoptera frugiperda (J E Smith)], a moth native to America, has spread throughout the world since it was first discovered in Africa in 2016. The FAW is a polyphagous migratory pest that can travel over long distances using seasonal winds or typhoons because of its excellent flying ability, causing serious damage to many crops. For effective FAW control, accurate species identification is essential at the beginning of the invasion. In this study, the FAW-specific gene Sf00067 was discovered by performing bioinformatics to develop a fast and accurate tool for the species-specific diagnosis of this pest. An Sf00067 loop-mediated isothermal amplification (LAMP) assay was developed, and optimal conditions were established. The Sf00067 6 primer LAMP (Sf6p-LAMP) assay established in this study was able to diagnose various genotype-based strains of FAW captured in Korea and FAWs collected from Benin, Africa. Our FAW diagnostic protocol can be completed within 30 min, from the process of extracting genomic DNA from an egg or a 1st instar larva to species determination.